The role of subicular place cells in spatial information processing : effects of variations in visual information, arena size and open field compartmentalisation - Brotons-Mas, Jorge R. (Trinity College (Dublin, Ireland). School of Psychology, 2008)
The hippocampal formation is involved in different cognitive processes such as learning, memory and spatial navigation. One of the landmark findings in neuroscience was the discovery of hippocampal place cells (PCs) -neurons which seem to code for spatial location in rodents and humans. In previous research, it was found that "place cells" were also present in different substructures of the hippocampal formation such as the subiculum or the entorhinal cortex. During the last few years, studies of the properties of place cells in the hippocampus proper have been many but somehow the study of other relevant areas, like the subiculum, has been neglected.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin